An Extended Unified Theory of Acceptance Model to Explain the Adoption of Electronic Payment System in Malaysia: A Conceptual Framework - Tamsin ROSMAINI; Ishaq JAAFAR (Communications of International Proceedings, 2020)
As the level of adoption toward electronic is becoming stringent, certain factors are considered influential toward such behavior.  This paper attempts to propose the key factors that affect the adoption of electronic payment system in Malaysia and the mediating factor that influence of each one of the factors in Malaysia. It offers a comprehensive framework that broadens the existing UTAUT model with important constructs such as government incentive and the mediating role mobile device proficiency. An extensive systematic literature review of the literature relating to electronic payment adoption was conducted. Lastly, this study settled on a conceptual model after reviewing previous studies and recommend an empirical investigation for validation in future for researchers and practitioners. Discussions and conclusions including academic and practical implications are also presented.
Keywords: Electronic Wallet; Technology Adoption; User’s Intention; Mobile Device Proficiency; Technology Skills.